Analysis of deoxynivalenol and deoxynivalenol-3-glucosides content in Canadian spring wheat cultivars inoculated with Fusarium graminearum. Issue 7 (2nd July 2016) - Amarasinghe, Chami C.; Simsek, Senay; Brûlé-Babel, Anita; Fernando, W. G. Dilantha
ABSTRACT: Contamination of wheat grains with Fusarium mycotoxins and their modified forms is an important issue in wheat industry. The objective of this study was to analyse the deoxynivalenol (DON) and deoxynivalenol-3-glucosides (D3G) content in Canadian spring wheat cultivars grown in two locations, inoculated with a mixture of 3-acetyldeoxynivalenol (3-ADON)-producing Fusarium graminearum strains and a mixture of 15-acetlyldeoxynivalenol (15-ADON)-producing F. graminearum strains. According to the analysis of variance, significant differences were observed among the cultivars for Fusarium head blight (FHB) disease index, Fusarium -damaged kernel percentage (%FDK), DON content and D3G content. When the effect of chemotype was considered, significant differences were observed for FHB disease index, FDK percentage and DON content. The D3G content and D3G/DON ratio were not significantly different between the chemotypes, except for D3G content at the Winnipeg location. The Pearson correlation coefficient between DON and D3G was 0.84 and 0.77 at Winnipeg and Carman respectively. The highest D3G/DON ratio was observed in cultivars Carberry (44%) in Carman and CDC Kernen (63.8%) in Winnipeg. The susceptible cultivars showed lower D3G/DON ratio compared with the cultivars rated as moderately resistant and intermediate. The current study indicated that Canadian spring cultivars produce D3G upon Fusarium infection.